Disaster plant pathology: Smart solutions for threats to global plant health from natural and human-driven disasters - Etherton, B.A.; Choudhury, R.A.; Alcalá-Briseño, R.I.; Mouafo-Tchinda, R.A.; Sulá, A.I.P.; Choudhary, M.; Adhikari, A.; Lei, S.; Kraisitudomsook, N.; Buritica, J.R.; Cerbaro, V.A.; Ogero, K.; et al. (Scientific Societies, 2024)
Disaster plant pathology addresses how natural and human-driven disasters impact plant diseases, and the requirements for smart management solutions. Local to global drivers of plant disease change in response to disasters, often creating environments more conducive to plant disease. Most disasters have indirect effects on plant health through factors such as disrupted supply chains and damaged infrastructure. There is also the potential for direct effects from disasters, such as pathogen or vector dispersal due to floods, hurricanes, and human migration driven by war. Pulse stressors such as hurricanes and war require rapid responses, while press stressors such as climate change leave more time for management adaptation but may ultimately cause broader challenges. Smart solutions for the effects of disasters can be deployed through digital agriculture and decision support systems supporting disaster preparedness and optimized humanitarian aid across scales. Here we use the disaster plant pathology framework to synthesize the effects of disasters in plant pathology and outline solutions to maintain food security and plant health in catastrophic scenarios. We recommend actions for improving food security before and following disasters, including (1) strengthening regional and global cooperation, (2) capacity building for rapid implementation of new technologies, (3) effective clean seed systems that can act quickly to replace seed lost in disasters, (4) resilient biosecurity infrastructure and risk assessment ready for rapid implementation, and (5) decision support systems that can adapt rapidly to unexpected scenarios.